Nitrógeno, fósforo y cociente C/N en los sedimentos superficiales de la laguna de Chacopata, Sucre, Venezuela - Fuentes Hernández, María Valentina (2000)
The basal behaviour and relationship with organic carbon (Corg) content and prevailing granulometric fractions, of organic nitrogen (Norg), total phosphorus (P-total) and C/N ratio in surface sediments of Chacopata lagoon, Sucre State, Venezuela, Were studied. Concentrations and spatial gradients were determined in sixteen stations following a common method for marine sediments. Norg concentrations varied between 0.102 and 0510% (x = 0.237%), total phosphorus between 0.012 and 0.094% (X = 0.058%) and C/N ratio between 9.27 and 44.47 (x = 20.53). The higher contents of Norg and total phosphorus are from sections with an.abundance of mangroves, marine phanerogams, macroalgae, benthonic biomass and migratory birds shelters. The C/N ratio shows the typical values for carbonated sediments, indicating that the nitrogenous compounds are rapidly degraded and the organic matter presents itself as humic substances. This parameter was moderately associated with silt and clay, and showed antagonism with sand, whereas Norg and phosphorus showed no correlation with them. The organic contribution is purely autochthonous: no anthropogenous contributions were found.